On-chip lens-less holographic trichoscopy / trichometry technologies: microinterferometric, Fourier spectral and correlographic techniques for clinical trichology. - O. V. Gradov; P. A. Nasirov; A. A. Goncharova; V. K. Fischenko; A. G. Jablokov (Морфологія, 2018)
The novel principle of trichomorphological analysis is provided. This principle, which may be interpreted as a transition between trichoscopy and trichometry, was developed using methods and techniques, explicated from the lens-less holographic microscopy, lens-lens tomography and filtering / decomposition of microscopic images based on orthogonal transformations, such as the FFTW-library-assisted DFT using Bluestein's FFT algorithm (expresses the Chirp Z-transform as a convolution and implements it efficiently using FFT/IFFT), Rader's FFT algorithm (from MIT Lincoln Laboratory) and Cooley–Tukey FFT algorithm (corresponding to different factorizations and / or different memory-access patterns). It is possible, that such methods can be applicable not only for clinical diagnostics, but also for some specialized trichological investigations, including fast and strong determination of different descriptors for ethnomedicine, gender and hormonal or endocrinology-relevant differences, prenatal and neonatal trichology, bio-archaeometric analysis, including palaeotrichology, and criminological trichomorphology, analysis of efficiency of some pharmaceutical and toxicological agents and events (including microelement status) for different psychosomatic cases, etc. The principal schemes of the laser holographic trichometry setups also may be based on a principles of the combined reflection and transmission lens-less microscopes, on-chip differential interference contrast microscopy, lensless wide-field fluorescent imaging on a chip, off-axis holography and lensless incoherent holography, ulttaviolet microscopy, including deep-UV spectral range.